Party Membership and Activism in a New Democracy: Evidence from the Portuguese Case - Espírito Santo, Paula (2021)
While the analysis of party models and types of party members has been widely discussed at the theoretical level, empirical research has not attracted similar attention. This study contributes to filling this gap by examining an understudied case, namely party members in Portuguese political parties. The key objective of this article is to make a contribution to the study of activism and dedication to the party, in a comparative perceptive, considering different types of parties. The survey applied was based on an on-line questionnaire conducted within the MAPP (Members and Activists of Political Parties) research network. The dataset included members of several parties ranging from typical catch-all parties (PS - Socialist Party; PSD - Social Democratic Party) to elite-based types (CDS-PP - Social Democratic Centre-Popular Party), as well as 'movement' party types (BE - Left Bloc; LIVRE). The study covers four main dimensions of party membership: party members' socio-demographic profile, ideological attitudes, reasons for joining the party, and activism levels and types. We show that party membership in Portugal follows similar trends to other advanced European democracies, albeit with important differences between parties. These results are an important barometer for measuring the quality of democracy, especially one as young as Portugal's.